Eating habits and physical activity of health area university in the municipality of Petrolina-PE. - Marianne Louise Marinho Mendes; Fernanda Rodrigues da Silva; Cristhiane Maria Bazílio de Omena Messia; Paulo Gustavo Serafim de Carvalho; Tarcísio Fulgêncio Alves da Silva (Universidade de Brasília, 2016)
The research aimed to know the eating habits and level of physical activity of students in the first and final year of health courses at the University of Pernambuco, Petrolina Campus. This - is a cross-sectional study, descriptive and observational, conducted with students of nutrition courses, physiotherapy and nursing at the University of Pernambuco (UPE), Petrolina campus. The instruments used were the questionnaire "How is your food?" Proposed by the Ministry of Health and the adapted International Physical Activity Questionnaire (International Physical Activity Questionnaire). The sample consisted of 155 academics from the university health courses, of which 102 (65.8%) were freshmen and 53 (34.2%) seniors. With a predominance of females. The average age was 21.7 (± 3.5) years. Students have had an inadequate intake of fruit. The consumption of vegetables was within the standard daily recommendations for this group of foods. Regarding the water intake among the participants, it has to be 72.26% of them do not drink the recommended amount, there was a significant difference (p